2011
DOI: 10.1227/neu.0b013e318214abbd
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of Endovascular Coiling of Wide-Necked Aneurysms Using Double Stents in a Y Configuration

Abstract: Y-stent reconstruction enables the endovascular management of otherwise complex, wide-necked cerebral aneurysms and can be performed safely in experienced hands with satisfactory mid-term results, even in cases requiring retreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 14 publications
2
102
2
1
Order By: Relevance
“…These excellent results demonstrated the efficacy and durability of the Y-stent technique for intracranial bifurcation aneurysms, which coincided with the findings in recently published literature. 21,22 In this series, the success rate of the techniques associated with the crossing-Y or kissing-Y stent was 100%. Although a thrombus event (1/11) resulting from a coil loop protrusion was encountered in case 2 (Fig 1), a salvaging Y-stent was used, achieving the patency of double branches.…”
Section: Efficacy and Safety Of The Y-stent Techniquementioning
confidence: 67%
“…These excellent results demonstrated the efficacy and durability of the Y-stent technique for intracranial bifurcation aneurysms, which coincided with the findings in recently published literature. 21,22 In this series, the success rate of the techniques associated with the crossing-Y or kissing-Y stent was 100%. Although a thrombus event (1/11) resulting from a coil loop protrusion was encountered in case 2 (Fig 1), a salvaging Y-stent was used, achieving the patency of double branches.…”
Section: Efficacy and Safety Of The Y-stent Techniquementioning
confidence: 67%
“…Results from several smaller series have suggested efficacy and safety with the use of overlapping-stent constructs. 3,8,30 Chalouhi et al 4 reported no complications in 28 patients with overlapping stents. Our study may include the largest series of overlapping-stent treatments for aneurysms.…”
Section: Stent Configurationmentioning
confidence: 98%
“…1 Fargen et al 8 combined the single-center experiences of 7 institutions and found that among 45 patients treated with Y-configuration stenting, 3 (7.5%) of 40 had a modified Rankin Scale score of ≥ 3 at follow-up. Spiotta et al 30 reported 4 clinically significant strokes in a series of 19 patients with Y-stented aneurysms, 3 (15.8%) of which seemed to be major complications. Chalouhi et al 5 reported 1 significant complication (6.3%) in 16 basilar tip aneurysms treated with Y-configuration stenting.…”
Section: Stent Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various configurations of stentings have been proposed and performed for bifurcation aneurysms, including a single stent from a proximal to a distal vessel; a waffle-cone stent 6 ; a horizontal stent [7][8][9] ; a nonoverlapping-Y stent 10 ; a kissing (double-barrel) Y stent, in which both stents are deployed in a parallel fashion 11,12 ; and a crossing-Y stent, in which the second stent is deployed through the interstices of the first stent. [12][13][14][15][16][17][18] The differences in hemodynamics among these various configurations of stent placement are unclear, and this may be important for the recanalization rate. In crossing-Y stents, use of double closed-cell stents causes narrowing of the second stent through the interstices of the first stent, 17 while using an open-cell stent as the first stent can avoid this effect of narrowing.…”
mentioning
confidence: 99%